2019
DOI: 10.31004/obsesi.v4i1.338
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Pendidikan Matematika Realistik (PMR) dalam Meningkatkan Pemahaman Konsep Bilangan Cacah pada Anak Usia Dini

Abstract: Pendidikan matematika realistik adalah salah satu alternative pendekatan pembelajaran yang dapat dipilih untuk meningkatkan hasil belajar, karena pendekatan ini akan mampu menjembatani proses pembelajaran matematika yang abstrak menjadi mudah dan terasa manfaatnya. Penelitian ini bertujuan untuk menghasilkan gambaran pelaksanaan pembelajaran matematika untuk anak usia dini dengan menggunakan pendekatan PMR. Jenis penelitian yang digunakan adalah Penelitian Tindakan Kelas model siklus dari Jean McNiff. Hasil pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
4
0
3
Order By: Relevance
“…The results of the study (Widyastuti & Pujiastuti, 2014) show that there is a significant effect between learning mathematics and PMRI in learning mathematics with distance and speed material on understanding concepts and students' logical thinking for fifth grade of Elementary School group II in Umbulharjo District, Yogyakarta City. Research that has been carried out (Adjie, Putri, & Dewi, 2019). The result of learning is also aimed to understand the concept of numbers and learning in PAUD after using PMR have progressed very well, which is shown in the work on the assignment sheet which being answered correctly.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The results of the study (Widyastuti & Pujiastuti, 2014) show that there is a significant effect between learning mathematics and PMRI in learning mathematics with distance and speed material on understanding concepts and students' logical thinking for fifth grade of Elementary School group II in Umbulharjo District, Yogyakarta City. Research that has been carried out (Adjie, Putri, & Dewi, 2019). The result of learning is also aimed to understand the concept of numbers and learning in PAUD after using PMR have progressed very well, which is shown in the work on the assignment sheet which being answered correctly.…”
Section: Resultsmentioning
confidence: 96%
“…The results showed that: There is a significant influence between mathematics learning and Indonesian Realistic Mathematics Education on the understanding of students' concepts and logical thinking and understanding of student concepts (Widyastuti & Pujiastuti, 2014); (Adjie, Putri, & Dewi, 2019). Idris points out that mathematics learning with the RME approach has improved the results of learning mathematics (Nopiyani, Turmudi, Prabawanto, & S., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Matematika berperan penting dalam menata proses berpikir manusia dan mempercepat penguasaan ilmu teknologi, karena matematika sebagai sarana berpikir. Matematika harus dipandang sebagai proses berpikir (Adjie et al, 2020). Pengalaman awal matematika anak membentuk dasar untuk belajar matematika pada tahap selanjutnya.…”
Section: Pembahasanunclassified
“…Mengenal konsep bilangan termasuk dalam kemampuan berhitung permulaan pada anak usia dini (Adjie et al, 2019;Musi et al, 2017). Besar sekali pengaruh pemahaman konsep bilangan untuk anak.…”
Section: Introductionunclassified